KIPRAH WANITA JEPANG DALAM KELUARGANise Samudra Sasanti Fakultas Bahasa dan Sastra Universitas Negeri Surabaya, nissasanti@yahoo.co.id (Lentera, Jurnal Studi Perempuan, 2014)
Abstract:  The  assumption  that  Japanese  women  today  have  more  power  than  man and that the families of modern Japanese dominated and centered to the mother (or women)  is  quite  a  bit  contradictive.  Despite  such  surface  trends  towards  gender equality,  many  Japanese  women  still  following  the  traditional  gender  patterns  in Japanese  society.  For  instance,  women  have  to  walk  a  pace  behind  their  male partner or husband. Although there have been changes in the structured patterns of gender  in  both  the  family  and  the  workplace  which  enable  Japanese  woman  to actualise themselves in the society. A Japanese  woman still bound with traditional patterns; that a woman in her childhood must serve her father, in adult life devoted toher husband,  and in the old age subserve her son. Women in this case are really submissive and endurance to the men. Keywords: son, adult, old, submissive, endurance